OBJECTION MECHANISM TOWARDS DECISIONS OF THE CONSUMER DISPUTE RESOLUTION AGENCY IN FINANCING DISPUTES MOTOR VEHICLE - Adel Fitriyan Lubis; Padian Adi Salamat Siregar (Inspiring Law Journal, 2026)
Consumer disputes in motor vehicle financing often occur between consumers and business actors, especially regarding default, withdrawal of financing objects, and the application of standard clauses that are detrimental to consumers. To provide fast, simple, and low-cost dispute resolution, Law Number 8 of 1999 concerning Consumer Protection established the Consumer Dispute Resolution Agency (BPSK) as an out-of-court dispute resolution institution, but there is still a legal remedy for objections to the District Court which has the potential to raise legal certainty issues. This research is a normative legal research with a statutory approach and a case approach that aims to analyze the authority of BPSK, the mechanism for examining objections to BPSK decisions at the Medan District Court, and the form of legal protection for consumers and business actors.The research findings indicate that objections to BPSK decisions represent a form of judicial oversight by the District Court over the BPSK's authority and procedures. However, in practice, objection hearings often focus not only on legality and procedural aspects but also on reopening the underlying dispute, leading to inconsistent decisions and reducing legal certainty. Furthermore, the absolute boundaries of authority between the BPSK and the District Court in handling motor vehicle financing disputes remain unclear.